Contraceptive use of HIV-positive women attending an HIV treatment center in Osogbo, Nigeria - Samuel Olowookere; Akindele Ajayi; Ajibola Idowu; Adeola Ajayi; Babatunde Afolabi (Libyan International Medical University Journal)
Background: Access to combination antiretroviral therapy (ART) enables HIV-positive women to live longer in good health. Some of these women are sexually active having unintended pregnancies and unsafe abortions because of not using contraceptives. Objective: This study assessed pattern of contraceptive use by HIV-positive women of reproductive age group attending an HIV treatment center at Ladoke Akintola University of Technology Teaching Hospital, Osogbo, Nigeria. Materials and Methods: A descriptive cross-sectional study of 400 HIV-positive women that completed an interviewer-administered semi-structured questionnaire on awareness and use of contraceptives. Data collected were analyzed with SPSS version 17. Results: Majority, 217 (54.3%), had been pregnant since enrollment with 120 (55.3%) having an induced abortion. Majority, 378 (94.5%), were aware of contraception with health workers as the source of awareness being 204 (54%). Although 313 (82.8%) desire to use a contraceptive, 281 (74.3%) currently used a contraceptive with male condom, 130 (34.4%), being the most common type used. Selected factors significantly associated with contraceptive use included age 35 years and above (odds ratio [OR] =2.58, 95% confidence interval [CI] = 1.18–5.63, P = 0.018), higher education (OR = 4.48, 95% CI = 2.80–7.16, P = 0.0001), being unmarried (OR = 4.34, 95% CI = 2.74–6.88, P = 0.0001), skilled worker (OR = 4.64, 95% CI = 2.76–7.81, P = 0.0001), higher income (OR = 2.15, 95% CI = 1.20–3.82, P = 0.01), and increasing duration on highly active ART 6–12 months (OR = 8.88, 95% CI = 4.50–17.50, P = 0.0001) and >12 months (OR = 4.37, 95% CI = 2.27–8.43, P = 0.0001). Conclusions: Some sexually active HIV-positive women were not using contraceptives. It is necessary to increase contraceptive awareness and use among this vulnerable population.